A science literacy-oriented student worksheet development for Junior High School on the topic of waves and disasters - Siti Nur Atsma Atsma; Prasetyaningsih Prasetyaningsih; Vica Dian Aprelia Resti (Jurnal Pijar Mipa, 2022)
This study aims to explain the process of developing student worksheets and determine the level of validity of the developed student worksheets. The method used in this study is research and development (R&D) with a 4-D development model following Thiagarajan. This study was conducted in 3 stages: define, design, and develop. The instrument used in this study was a validation sheet filled out by teaching experts and science practitioners. The validation results gained 84.73% in the very valid category. The validation results on aspects of content feasibility, linguistic aspects, presentation aspects, and visual aspects respectively obtained an average percentage of 86.25%, 85.42%, 82.16%, and 90.63%, with very valid categories. The worksheets can be used for school science learning activities with a few revisions.